Time and its adversaries in the Seleucid empire - Kosmin, Paul J., 1984- (The Belknap Press of Harvard University Press, 2018)
Time and Resistance in the Seleucid Empire investigates the relationship between the formal temporal structures projected by the Seleucid imperial court and the indigenous temporalities that responded to, undermined, and ultimately resisted these. The complex and competing temporalities of the Hellenistic East - a site of intense creativity in conceptualizing time - have either been unnoticed in scholarship or treated in isolation. Understanding the interactions of these time systems as a coherent phenomenon of cultural and political history will provide new contexts and integrated explanations for questions central to both the classical Mediterranean world - such as post-Alexander state formation and "Hellenization"--And Near Eastern and religious studies - such as textual canonization and the emergence of apocalyptic theologies. The book's first half explores, above all, the invention and institutionalization of the Seleucid Era year count. This was the world's first continuous, irreversible, accumulating, and transcendent count of historical duration. The second part examines the Seleucid subjects' intellectual, religious, and political responses to this radically new temporal order. These include, most significantly, the first emergence of apocalyptic eschatology, that is, total histories of the world, from beginning to predicted end.--